Homoeopathic Management of Chronic Urinary Tract Infection (UTI) in Males—Two Evidence-Based Case Reports - Nanda, Jayashree; Prusty, Umakanta; Choudhury, Sujata (Homœopathic Links, 2024)
Urinary tract infections (UTI) are uncommon in men, with an incidence of 5 to 8 per 10,000 per year among those aged between 21 and 50 years, in contrast to women, where the incidence is 30 times higher. UTI in men can lead to severe and painful symptoms, often requiring surgical interventions. Considering the limitations and complications of conventional medical or surgical procedures, homeopathy may offer a viable solution for such conditions. Two cases of chronic UTIs in men are presented here, in which constitutional homeopathic medicines were prescribed with positive results. In the first case, the patient experienced frequent urination, urgency, straining before urination, and a drop-wise urine flow. A retrograde urethrogram X-ray diagnosed the condition as a stricture urethra. In the second case, the patient had been suffering from repeated UTIs with painful urination for two years and was diagnosed with cystitis and epididymo-orchitis. After detailed case assessments, both patients were prescribed constitutional homeopathic remedies. Sulphur was prescribed in the first case, and Arsenic in the second case, both in 50 millesimal potencies, providing relief within a short period. However, in both cases, Thuja was prescribed as complementary medicine, which cleared all UTI symptoms, leading to a negative urine culture result. Homeopathy proved effective in providing relief in two cases of chronic UTI. It's important to note that the conclusions drawn from these two cases may not be sufficient to reach a definitive conclusion. Therefore, clinical trials are suggested to establish the efficacy of constitutional medicine in the treatment of chronic UTIs in men.
Keywords: Arsenic; constitutional medicines; homoeopathy; Sulphur; urinary tract infections